Malleable Mara: Transformations of a Buddhist Symbol of Evil - Nichols, Michael D. (State University of New York Press, 2019)
Intro -- Contents -- List of Illustrations -- Note on Reprints -- Note on Translations -- Acknowledgments -- Abbreviations -- Chapter 1 Mapping out Mara -- Who is Mara? -- Defining Our Demon-God -- Approaching Mara -- Summary of the Book -- Chapter 2 Machinations of Māra: The Myriad Menaces of the Evil One -- Introduction -- The Categories of Mara's Representations in Pali Literature -- The Maravijaya: The Sources and Traditions of Mara's Battle with Gautama at Bodh-Gaya -- Is Mara Truly the "Evil One?": Mara and the Indian Concept of Evil -- Conclusion -- Chapter 3 Māra the Demon: Asura Ancestry -- Introduction -- Mara in a (Minor) Demonic Key -- Mara in the Style of V.tra -- Conclusion -- Chapter 4 Māra the God: Brahmanical Background -- Introduction -- Mara and Brahma: Delusions of Eternity -- Mara and Indra: Tyrants for the Social Order -- Mara and Kamadeva: The Mortification of Desire -- Mara and Yama: Dialogues with Death -- Conclusions -- Chapter 5 Māra's Metamorphosis: The Rise of the Mahāyāna and Its Impact on the Evil One -- Introduction -- A Threat around Every Corner: Mara in the Perfection of Wisdom Literature -- Old God, New Tricks: Mara and the Vimalakirti Sutra -- The Blurring of Both Worlds: Mara and the Sura.gamasamadhi Sutra -- Mara Mix and Match: The Nirva.a Sutra -- Conclusions -- Chapter 6 Māra Multiplied: The Evil One Across Asia -- Introduction -- Matching Meanings: Mara in China -- Anger is an Energy: Mara in Tibet -- Rule Global, Tempt Local: Mara in Southeast Asia -- Demons and Demonizing: Mara in Japan -- Conclusions -- Chapter 7 Go West, Evil God: Modernized Māra -- Introduction: Buddhist Studies and Buddhism in the West -- The Wave of the Future is the Past: Thoroughly Modernized Mara -- A Turn of the Screwtape: Using Mara to Critique Western Culture -- Big Demon, Small Screen: Mara on Doctor Who -- Conclusions.